Living with children with autistic spectrum condition: parental stress and the impact upon family functioning. - Dickinson, Kathleen; Place, Maurice (Advances in Social Sciences Research Journal, 2016)
Introduction. Parenting a child with Autistic Spectrum Condition (ASC) is both practically and emotionally challenging. The condition brings difficulties in communication and social interaction, as well as abnormal behaviour patterns, all of which have an impact upon parents. Method. As part of a larger study, one hundred mothers of children with ASC were asked to complete several scales including the Family Adaptation and Cohesion Evaluation Scale (FACES IV), and The Parenting Stress Index-Short form (PSI-SF). Results. The Parenting Stress Index scores showed that the mothers of the primary aged children felt very high levels of parental stress, and distress, while the mothers of secondary age children reported lesser levels. The FACES IV scores indicated that the sense of flexibility was higher in the mothers of adolescents, and that the families of girls were less cohesive than that of boys. Discussion. The highest level of parental stress was reported by the mothers of younger children, with the parenting of teenage girls being the most stressful. Conclusion. A family pattern which tends to seek smaller changes could reduce the sense of family distress that parents of children with ASC experience. As the children move into adolescence the mothers tend to feel less stressed, but less so for the mothers of teenage girls.